1973
DOI: 10.1073/pnas.70.12.3847
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of Ferritin Macromolecules. The Lattice Structure of the Core Crystallites

Abstract: The ultrastructure of the crystalline ferric mineral that forms the central core of ferritin macromolecules has been examined by means of ultrahigh resolution electron microscopy at 100 kV. Very high magnification dark-field images reveal the presence of either a single large crystal or several smaller crystallites within many of the cores. When the highly crystalline core contents are suitably oriented to transmit their Bragg reflections through the objective aperture, regular fringes separated by 2-9.5 A hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Towe and Bradley (1967) showed spherical aggregates formed by precipitation from ferric chloride and iron micelles within the ferritin macromolecule, both about 30-50 in diameter. Massover and Cowley (1973) similarly showed 50-~ spheres from horse-spleen ferritin. Natural ferrihydrites were also shown to be aggregates of 30-50-~ spheres (Schwertmann and Fischer, 1973;Henmi et al, 1980;Carlson and Schwertmann, 1981).…”
Section: Review Of Previous Workmentioning
confidence: 91%
See 2 more Smart Citations
“…Towe and Bradley (1967) showed spherical aggregates formed by precipitation from ferric chloride and iron micelles within the ferritin macromolecule, both about 30-50 in diameter. Massover and Cowley (1973) similarly showed 50-~ spheres from horse-spleen ferritin. Natural ferrihydrites were also shown to be aggregates of 30-50-~ spheres (Schwertmann and Fischer, 1973;Henmi et al, 1980;Carlson and Schwertmann, 1981).…”
Section: Review Of Previous Workmentioning
confidence: 91%
“…Russell (1979) has since shown that about half the hydrogen is present as OH; he suggested a formula Fe203 9 2FeO(OH).2.5H20. Massover and Cowley (1973) found TEM evidence for 9-/k lattice fringes crossed by 4.4-~ fringes in the cores of ferritin molecules, and regarded this as confirmation of the Towe and Bradley structure.…”
Section: Review Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These medicaments are often regarded as pharmaceutical analogues or model compounds of ferritin. The main differences between ferritin and its analogues are in the form of the iron core which is hexagonal ferrihydrite in ferritin and tetragonal β-FeOOH in the majority of analogues such as iron-dextran [5,6] as well as in the shell.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of physical techniques including X-ray and electron diffraction [6,7], high resolution transmission electron microscopy [8,9], EXAFS [10], EPR [11], NMR relaxometry [12,13], magnetic measurements [14][15][16][17], and M/Sssbauer spectroscopy [10, 14,[18][19][20][21][22][23][24][25][26] have been used to study the properties of the ferric oxy-hydroxide core particles of ferritin. The particles consist of the quasicrystalline, ferric-hydrous-oxide mineral, ferrihydrite.…”
Section: Introductionmentioning
confidence: 99%